The DIRFloortime Approach in Speech Therapy for Speech Development in Children with ADs and Other Disorders. Recommendations for Parents and Teachers - E.S. Gomozova; M.A. Gomozova (Moscow State University of Psychology and Education, 2019)
The "RecheTsvetik" center offers an intervention program based on the DIRFloortime developmental approach for speech development in children with autism spectrum disorders. The main rule when working with a child is to help him learn how to use ideas and words and to associate words and ideas of a parent or a teacher with his own desires and intentions. This article provides recommendations and techniques used by DIR speech therapists to develop speech in children with autism spectrum disorders and is intended for parents and teachers.